2020
DOI: 10.2478/manment-2019-0049
|View full text |Cite
|
Sign up to set email alerts
|

Job stress and organizational citizenship behavior among university teachers within Bangladesh: mediating influence of occupational commitment

Abstract: SummaryThis study aims to explore the impact of job stress on organizational citizenship behavior (OCB) among university teachers in Bangladesh along with the mediating effect of occupational commitment (OC) on this relationship. An online questionnaire survey using the Google form was conducted to collect data from respondents. 244 valid samples were analyzed using bivariate correlation and regression analyses. The results of hierarchical regression analyses reveal that job stress is negatively and significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In addition, the university requires a lot of extra administrative work as it follows the Thai Quality Framework (TQF) for quality control. Teachers sometimes have to fulfill their family responsibilities and it is difficult for them to have a positive attitude towards the tiring and routine paperwork and documentation (Amin et al, 2020;Cheasakul & Varma, 2016).…”
Section: Organizational Commitment and Ocb In The University Environmentmentioning
confidence: 99%
“…In addition, the university requires a lot of extra administrative work as it follows the Thai Quality Framework (TQF) for quality control. Teachers sometimes have to fulfill their family responsibilities and it is difficult for them to have a positive attitude towards the tiring and routine paperwork and documentation (Amin et al, 2020;Cheasakul & Varma, 2016).…”
Section: Organizational Commitment and Ocb In The University Environmentmentioning
confidence: 99%
“…JST causes negative perceptions of stimuli or the surroundings, inhibits access to resources and personal work, and negatively impacts the sense of humor, relationships with colleagues, and communication levels. Amin, et al [69] studied university lecturers in Bangladesh and found that JST had a statistically significant negative effect on OCB. Lecturers who were responsible for various assignments became stressed and did not exhibit positive behaviors.…”
Section: Development Of the Hypothesesmentioning
confidence: 99%
“…CSR activities help organizations improve their reputation and image in society, which are directly and indirectly linked to green HRM practices that focus on employees. An organization's reputation and image can influence job-seeker graduated students' intentions toward organizations prioritizing GHRM, CSR, and OR practices (Amin et al 2020, Ostic et al 2021. Traditional HRM practices that do not prioritize green strategies recruit only skilled workers to meet economic goals, resulting in low employee loyalty.…”
Section: Introductionmentioning
confidence: 99%